2022
DOI: 10.3390/ijms23020637
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CT Texture Analysis in Adrenal Masses: A Systematic Review

Abstract: Adrenal incidentalomas (AIs) are incidentally discovered adrenal neoplasms. Overt endocrine secretion (glucocorticoids, mineralocorticoids, and catecholamines) and malignancy (primary or metastatic disease) are assessed at baseline evaluation. Size, lipid content, and washout characterise benign AIs (respectively, <4 cm, <10 Hounsfield unit, and rapid release); nonetheless, 30% of adrenal lesions are not correctly indicated. Recently, image-based texture analysis from computed tomography (CT) may be usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
(107 reference statements)
1
16
0
5
Order By: Relevance
“…Recently, several papers have been published regarding to the application of radiomics in patients with adrenal lesions. Results coming from these studies, performed especially to discriminate benign from malignant lesions, appear to be very promising (23). Keeping in mind that approximately 50% of AIs produce more cortisol and about diagnostic pitfalls occurring in adrenal masses characterization, we speculate on the properties of radiomics to discriminate cortisolsecreting from not-secreting AIs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, several papers have been published regarding to the application of radiomics in patients with adrenal lesions. Results coming from these studies, performed especially to discriminate benign from malignant lesions, appear to be very promising (23). Keeping in mind that approximately 50% of AIs produce more cortisol and about diagnostic pitfalls occurring in adrenal masses characterization, we speculate on the properties of radiomics to discriminate cortisolsecreting from not-secreting AIs.…”
Section: Discussionmentioning
confidence: 92%
“…Up to now, most of radiomics studies have been performed in oncologic field with surprising results (7). Furthermore, as supported by the review from Crimì et al (23), encouraging data come from texture analysis in adrenal lesions. This study moves the field of application of radiomics in the context of functional adrenal disease trying to overcome some of the pitfalls described above, proposing it as a useful tool for clinical investigation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, another limit is that this study does not address the main radiologic diagnostic challenge regarding the adrenal glands, which is discriminating malignant from benign lesions. This is a potential use of texture analysis, which already demonstrated an accuracy up to 93% in this task [ 20 ]. However, this study aimed to give even more purpose to the data extracted in the setting of the studies regarding the discrimination of adrenal incidentalomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the latest evidence shows that texture analysis features based on CT and MRI images allow for differentiating malignant from benign adrenal lesions with good accuracy. If a suspected malignant or functioning form is found, a multidisciplinary team should plan an appropriate follow-up [ 15 ]. Moreover, recent studies reported that the inactivating variants in the ARMC5 (Amadilo repeats containing 5; OMIM 615,549) gene located on chromosome 16p11.2 are the most common genetic cause of PBMAH (primary bilateral macronodular adrenal hyperplasia), which is a rare type of Cushing syndrome characterized by the bilateral enlargement of the adrenal glands, large adrenal nodules (>10 mm), and increased cortisol production.…”
Section: Benign Lesionsmentioning
confidence: 99%